Bringing the Laser to the Product: Intelligent mobile laser marking system for Industry 4.0 production environments. Issue 2 (12th April 2017) - Steck, Dieter
Abstract: Highly agile, self‐organizing industrial 4.0 production environments require an extremely high level of intelligence and networking of all process relevant factors. Not to be underestimated in this context is the integration of laser marking systems, which ensure a safe, durable marking, and therefore a definite traceability of the produced parts or products. Optical part recognition and individual laser marking as part of the automatized production may already be state of the art, however, the list of requirements for lasers for surface marking continues to grow — especially with regards to the laser's flexibility and cost effectiveness.